Psychosocial Factors as Predictors of Academic Behavioural Confidence among Pre-Medical Students of University of Ibadan - Odedokun, Solomon Adekunle (European Scientific Journal, ESJ, 2022)
Academic behavioural confidence is an important non-cognitive factor which has a significant tendency to influence students’ academic achievement and future aspirations. When an individual has little or no self-confidence in his academic pursuit, it could lead to frustration, low self-esteem, depression, and emotional distress which could eventually result to academic failure. If academic behavioural confidence is as important as stated above, then there is a need to investigate the predicting factors of the concept. This study, therefore, focuses on the role of parental support, achievement motivation, emotional intelligence, religiosity, and psychological adjustment on academic behavioural confidence among pre-medical students of University of Ibadan. The descriptive research design was adopted for this study, using the ex-post facto type. Two hundred (200) pre-medical students of University of Ibadan were randomly selected. Data collected were analysed using Pearson Product Moment Correlation (PPMC) and multiple regression at 0.05 level of significance. The result revealed that there is a significant relationship between the independent and dependent variables among pre-medical students of University of Ibadan. In terms of magnitude, achievement motivation was the strongest predictor (β = .332, t = 5.287, p < 0.01), followed by religiosity (β = .308, t = 5.272, p < 0.01), psychological adjustment (β = .185, t = 3.279, p < 0.05), and emotional intelligence (β = .184, t = 2.937, p < 0.05). Based on the findings, it is therefore recommended that since achievement motivation has been found to be the strongest predictor of academic behavioural motivation among the participants, parents (most especially) and others who share close ties with the students should motivate the students to achieve their desired goals and aspirations. Teachers and lecturers could also intrinsically motivate the students through their positive and constant words of encouragement all through the tedious academic and medical training. Such re-assuring words like “It is not hard”, “I did it, you can also do it” would alleviate the fear of failure.